The role of neuronal calcium sensors in balancing synaptic plasticity and synaptic dysfunction - Kerrigan, Talitha L.; Whitcomb, Daniel; Regan, Philip; Cho, Kwangwook (Frontiers in Molecular Neuroscience, 2012)
Neuronal Calcium Sensors (NCS) readily bind calcium and undergo conformational changes enabling them to interact and regulate specific target molecules. These interactions lead to dynamic alterations in protein trafficking that significantly impact upon synaptic function. Emerging evidence suggests that NCS and alterations in Ca2+ mobilization modulate glutamate receptor trafficking, subsequently determining the expression of different forms of synaptic plasticity. In this review we aim to discuss the functional relevance of NCS in protein trafficking and their emerging role in synaptic plasticity. Their significance within the concept of ‘translational neuroscience’ will also be highlighted, by assessing their potential as key molecules in neurodegeneration.